Ruthenium-cobalt solid solution oxide nanofiber material as well as preparation method and application thereof
Ruthenium cobalt solid solution oxide nanofiber materials prepared by electrospinning technology solve the problem of insufficient efficiency and stability of existing electrocatalysts under high current density, and realize high-efficiency alkaline electrocatalytics under industrial-grade conditions. Excellent HER and OER performance and long-term stability.
Patent Information
- Application Number
- CN202411577328.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Existing electrocatalysts exhibit low efficiency and instability at high current density, making it difficult to effectively perform alkaline electrolytic water decomposition under industrial-grade conditions, especially in dual-function applications of HER and OER, lacking efficient and stable solid solution nanos Fiber material.
Using electrospinning technology to prepare ruthenium cobalt solid solution oxide nanofiber materials in air atmosphere calcination, forming a rough and uniform fiber morphology, increasing the exposure of active sites and optimizing electron transport performance, suitable for alkaline electricity under industrial-grade current density catalytic.
It realizes efficient and stable HER and OER catalysis at industrial-grade current density, reduces the overpotential demand, and maintains high stability within 120 hours, which is suitable for practical industrial applications.
Smart Images

Figure CN119265626A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid solution nano material preparation, and specifically relates to a ruthenium cobalt solid solution oxide nano fiber material and a preparation method thereof, and application of the material in alkaline electrocatalytic hydrogen and oxygen evolution at industrial-grade current density. Background Art
[0002] Nowadays, electrocatalytic water splitting technology is considered to be an efficient, feasible and promising green hydrogen production method due to its economic, clean and environmental advantages. It is foreseeable that this technology can significantly solve the problems of environmental pollution and energy crisis faced by mankind. However, low efficiency, high overpotential and excessive use of precious metals lead to expensive hydrogen production costs. On the other hand, some of the currently developed efficient hydrogen evolution (HER) and oxygen evolution (OER) electrocatalysts are mainly used at low current density (<100mA / cm 2 ) and cannot be used at high current densities (≥1000mA / cm 2 ) conditions. In addition, poor stability at high current density has also become a key obstacle to its practical application. Therefore, an ideal alkaline water electrolyzer requires not only excellent HER and OER activities, but also stability when operating at high current density.
[0003] In general, to improve the HER and OER performance of electrocatalysts, creating more exposed active sites and improving electron transport and mass transfer processes are important conditions. Nanofibers are ideal candidate materials for HER and OER electrocatalysts because of their advantages in this regard. On the other hand, modulating the electronic structure of electrocatalysts is considered to be an effective method to improve their electrocatalytic activity. Recently, metal oxide solid solutions have been shown to be efficient OER electrocatalysts. For example, in ruthenium manganese oxide solid solutions with a rutile structure, strong electron transfer from ruthenium to manganese sites causes the atomic charge of the ruthenium sites to be more positive, thereby contributing to excellent acidic OER performance (J. Mater. Chem. A, 2023, 11, 25252). However, there are currently no reports on the application of solid solution nanofiber-based electrocatalysts in achieving alkaline bifunctional HER and OER at high current density. To this end, the present invention combines the advantages of nanofibers and solid solution structures to prepare alkaline HER and OER bifunctional electrocatalysts with high activity and stability that can be applied to electrolysis of water at industrial current density, laying the foundation for the practical application of electrolysis of water. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a highly efficient and stable ruthenium cobalt solid solution oxide nanofiber material and its preparation method and application in alkaline electrocatalysis HER and OER at industrial current density. The present invention adopts electrospinning technology combined with air atmosphere calcination to prepare ruthenium cobalt solid solution oxide nanofiber material, which has a rough and uniform fiber morphology as a whole, has a large number of exposed active sites and excellent electron transport performance.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a ruthenium-cobalt solid solution oxide nanofiber material, the steps of which are as follows:
[0007] A. Preparation of nanofiber membrane by electrospinning:
[0008] A1. Dissolve 0.2-0.4 g polyvinyl pyrrolidone, a certain mass of cobalt salt and ruthenium salt in 2-5 mL of a mixed solution of N,N-dimethylformamide and ethanol, wherein the amount of N,N-dimethylformamide or ethanol can be 0, and stir for 12 hours to obtain a uniform viscous spinning solution precursor;
[0009] A2, injecting the viscous spinning solution precursor in step A1 into the syringe of the electrospinning device, performing electrospinning at a spinning distance of 15 to 30 cm and a spinning voltage of 12 to 25 kV, and obtaining a nanofiber membrane on an aluminum foil receiving plate;
[0010] Step B: calcining the nanofiber membrane obtained in step A2 in air at 200-500° C. for 2-4 hours to obtain a ruthenium-cobalt solid solution oxide nanofiber material.
[0011] Furthermore, in step A1, the mass ratio of the total mass of the cobalt salt and the ruthenium salt to the polyvinyl pyrrolidone is 1:1;
[0012] Further, in step A1, the molar ratio of the cobalt salt to the ruthenium salt is 1:(1-3);
[0013] Furthermore, in step A1, the cobalt salt is one of cobalt acetate, cobalt nitrate or cobalt chloride; the ruthenium salt is one of potassium chlororuthenate, ruthenium chloride or ammonium chlororuthenate;
[0014] Furthermore, the molecular weight of polyvinyl pyrrolidone in step A1 is 1000-1500 kDa.
[0015] In a second aspect, the present invention provides a ruthenium-cobalt solid solution oxide nanofiber material, which is prepared by any one of the above technical solutions;
[0016] Furthermore, the ruthenium-cobalt solid solution oxide nanofiber is a one-dimensional material with a diameter of 100 to 400 nm and a length greater than 5 μm;
[0017] In a third aspect, the present invention provides an application of a ruthenium-cobalt solid solution oxide nanofiber material in alkaline electrocatalytic hydrogen and oxygen evolution at industrial-grade current density.
[0018] Beneficial effects of the present invention:
[0019] 1. The ruthenium-cobalt solid solution oxide nanomaterial provided by the present invention has a rough and uniform fiber morphology as a whole, has a large number of exposed active sites and excellent electron transport performance.
[0020] 2. The preparation method of the ruthenium cobalt solid solution oxide provided by the present invention is simple, easy, low-cost and has a short preparation cycle, and is expected to achieve industrial large-scale production.
[0021] 3. The ruthenium-cobalt solid solution oxide nanofiber material provided by the present invention can be used as a bifunctional catalyst for water electrolysis at industrial-grade current density. By adjusting the ratio of ruthenium and cobalt elements, it exhibits excellent catalytic activity, effectively improves the stability of the reaction and reduces the overpotential required for the reaction. Its electrocatalytic HER and OER current density reaches 1A / cm 2 When , the required overpotential is only 149mV and 362mV respectively, and the catalytic stability reaches 120h, which meets the needs of practical industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art; obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a scanning electron microscope image of the ruthenium cobalt solid solution oxide nanofiber prepared in Example 1;
[0024] Figure 2 is an X-ray diffraction pattern of the ruthenium cobalt solid solution oxide nanofibers prepared in Example 1;
[0025] Figure 3 A comparison diagram of polarization curves of the OER process of the ruthenium cobalt solid solution oxide nanofiber material prepared in Example 1, the ruthenium dioxide nanofiber material prepared in Comparative Example 1, and the cobalt tetraoxide nanomaterial prepared in Comparative Example 2;
[0026] Figure 4A comparison diagram of polarization curves of the HER process of the ruthenium cobalt solid solution oxide nanofiber material prepared in Example 2, the ruthenium dioxide nanofiber material prepared in Comparative Example 1, and the cobalt oxide nanomaterial prepared in Comparative Example 2;
[0027] Figure 5 The time-current curve of the ruthenium cobalt solid solution oxide nanofibers prepared in Example 1 for the OER process;
[0028] Figure 6 This is a time-current curve of the HER process of the ruthenium cobalt solid solution oxide nanofiber prepared in Example 2; DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below. Preferred embodiments of the present invention are given in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. It should be understood that the attached claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.
[0030] Example 1
[0031] 0.3g polyvinyl pyrrolidone (molecular weight 1300kDa), 0.1125g cobalt acetate and 0.1875g ruthenium chloride (molar ratio 1:2) were dissolved in a mixed solution of 1.8mL N,N-dimethylformamide and 1.8mL ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20cm and a spinning voltage of 18kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst, and the product was in the form of a black film.
[0032] Example 2
[0033] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1636 g of cobalt acetate and 0.1364 g of ruthenium chloride (molar ratio of 1:1) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst, and the product was in the form of a black film.
[0034] Example 3
[0035] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1000 kDa), 0.086 g of cobalt acetate and 0.214 g of ruthenium chloride (molar ratio of 1:3) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst, and the product was in the form of a black film.
[0036] Example 4
[0037] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.175 g of cobalt nitrate and 0.125 g of ruthenium chloride (molar ratio of 1:1) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0038] Example 5
[0039] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.125 g of cobalt acetate and 0.175 g of ammonium chlororuthenate (molar ratio of 1:1) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0040] Example 6
[0041] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 400°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0042] Example 7
[0043] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined in air at 200°C for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0044] Example 8
[0045] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 20 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0046] Example 9
[0047] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in 3.6 mL of N,N-dimethylformamide, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0048] Example 10
[0049] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in 3.6 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0050] Embodiment 11
[0051] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1300 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in a mixed solution of 1.5 mL of N,N-dimethylformamide and 1.5 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0052] Example 12
[0053] 0.3 g of polyvinyl pyrrolidone (molecular weight of 1500 kDa), 0.1125 g of cobalt acetate and 0.1875 g of ruthenium chloride (molar ratio of 1:2) were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300°C in air for 2 hours to obtain a ruthenium cobalt solid solution oxide nanofiber material catalyst.
[0054] Embodiment 13
[0055] The ruthenium cobalt solid solution oxide nanofiber catalyst prepared in Examples 1 and 2 was dispersed in a mixed solution of water, ethanol and Nafion (the mass ratio of water, ethanol and Nafion was 490:490:20) to prepare a dispersion with a concentration of 4 mg / mL; then 22.5 μL of the dispersion was dropped on a carbon paper with an area of 9 mm2 and dried naturally in the air to obtain a carbon paper loaded with the catalyst; the prepared carbon paper was tested in an electrolytic cell, and the test system was a three-electrode system (the carbon paper loaded with the catalyst was the working electrode, the carbon rod (for HER test) or the platinum wire (for OER test) was the counter electrode, and the mercuric oxide electrode (Hg / HgO) was the reference electrode), and the electrolyte was a 1 mol / L KOH solution. Before the test, Ar was passed into the electrolytic cell until saturation, and the Ar atmosphere was always maintained during the test. The OER and HER activities were evaluated respectively, and polarization curve tests (LSV) were performed at a scanning rate of 2 mV / s. At the same current density, the greater the overpotential, the lower the ability to produce oxygen and hydrogen. It should be noted that all potentials obtained with the mercuric oxide reference electrode in the electrocatalytic test were converted into reversible hydrogen electrode potentials in the property diagram, and the external power supply was the main battery of the electrochemical workstation.
[0056] Embodiment 14
[0057] The ruthenium cobalt solid solution oxide nanofiber catalyst prepared in Example 3 was dispersed in a mixed solution of water, ethanol and Nafion (the mass ratio of water, ethanol and Nafion was 490:490:20) to prepare a dispersion with a concentration of 4 mg / mL; then 22.5 μL of the dispersion was dropped on an area of 9 mm 2 The prepared carbon paper was placed on carbon paper and dried naturally in the air to obtain carbon paper loaded with catalyst; the prepared carbon paper was tested in an electrolytic cell, the test system was a three-electrode system (the carbon paper loaded with catalyst was the working electrode, the carbon rod (for HER test) or platinum wire (for OER test) was the counter electrode, and the mercuric oxide electrode (Hg / HgO) was the reference electrode), and the electrolyte was a 1 mol / L KOH solution. Before the test, Ar was passed into the electrolytic cell until saturation, and the Ar atmosphere was always maintained during the test. The OER and HER activities were evaluated separately, and polarization curve tests (LSV) were performed at a scan rate of 2 mV / s.
[0058] Comparative Example 1
[0059] First, 0.3 g of polyvinyl pyrrolidone (molecular weight 1300 kDa) and 0.3 g of ruthenium chloride were dissolved in a mixed solution of 1.8 mL of N,N-dimethylformamide and 1.8 mL of ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was carried out under the conditions of a spinning distance of 20 cm and a spinning voltage of 18 kV to obtain a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300 ° C in air for 2 hours to obtain a product, a ruthenium dioxide nanofiber material catalyst, and the product was a nanofiber with the same morphology as Example 1.
[0060] Comparative Example 2
[0061] First, 0.3g polyvinyl pyrrolidone (molecular weight 1300kDa) and 0.3g cobalt acetate were dissolved in a mixed solution of 1.8mL N,N-dimethylformamide and 1.8mL ethanol, and then stirred for 12 hours to obtain a uniform viscous spinning liquid precursor; the spinning liquid precursor was injected into the syringe of the electrospinning device, and electrospinning was performed under the conditions of a spinning distance of 20cm and a spinning voltage of 18kV, thereby obtaining a nanofiber membrane on an aluminum foil receiving plate; the obtained nanofiber membrane was calcined at 300℃ in air for 2 hours to obtain the product cobalt oxide nanomaterial. The product exhibits a morphology of coexistence of nanofibers / nanoparticles.
[0062] Comparative Example 3
[0063] The ruthenium dioxide nanofiber material catalyst prepared in Comparative Example 1 was dispersed in a mixed solution of water, ethanol and Nafion (the mass ratio of water, ethanol and Nafion was 490:490:20) to prepare a dispersion with a concentration of 4 mg / mL; then 22.5 μL of the dispersion was dropped on a 9 mm 2 The prepared carbon paper was placed on carbon paper and dried naturally in the air to obtain carbon paper loaded with catalyst; the prepared carbon paper was tested in an electrolytic cell, the test system was a three-electrode system (the carbon paper loaded with catalyst was the working electrode, the carbon rod (for HER test) or platinum wire (for OER test) was the counter electrode, and the mercuric oxide electrode (Hg / HgO) was the reference electrode), and the electrolyte was a 1 mol / L KOH solution. Before the test, Ar was passed into the electrolytic cell until saturation, and the Ar atmosphere was always maintained during the test. The OER and HER activities were evaluated separately, and polarization curve tests (LSV) were performed at a scan rate of 2 mV / s.
[0064] Comparative Example 4
[0065] The cobalt tetraoxide nanomaterial catalyst prepared in Comparative Example 2 was dispersed in a mixed solution of water, ethanol and Nafion (the mass ratio of water, ethanol and Nafion was 490:490:20) to prepare a dispersion with a concentration of 4 mg / mL; then 22.5 μL of the dispersion was dropped on a 9 mm 2 The prepared carbon paper was placed on carbon paper and dried naturally in the air to obtain carbon paper loaded with catalyst; the prepared carbon paper was tested in an electrolytic cell, the test system was a three-electrode system (the carbon paper loaded with catalyst was the working electrode, the carbon rod (for HER test) or platinum wire (for OER test) was the counter electrode, and the mercuric oxide electrode (Hg / HgO) was the reference electrode), and the electrolyte was a 1 mol / L KOH solution. Before the test, Ar was passed into the electrolytic cell until saturation, and the Ar atmosphere was always maintained during the test. The OER and HER activities were evaluated separately, and polarization curve tests (LSV) were performed at a scan rate of 2 mV / s.
[0066] Figure 1 This is a scanning electron microscope (SEM) image of the ruthenium cobalt solid solution oxide nanofiber prepared in Example 1. It can be seen that the material is a one-dimensional nanofiber with a rough surface and uniform diameter, with a diameter of 150-300 nm and a length greater than 5 μm.
[0067] Figure 2 This is an X-ray diffraction (XRD) pattern of the ruthenium cobalt solid solution oxide nanofibers prepared in Example 1. It can be seen that the main body of the obtained product is a solid solution phase of ruthenium cobalt oxide.
[0068] Figure 3The linear sweep voltammetric polarization curves of OER in potassium hydroxide (1MKOH) solution of the ruthenium cobalt solid solution oxide nanofiber material catalyst prepared in Example 1, the ruthenium dioxide nanofiber material catalyst prepared in Comparative Example 1, and the cobalt tetraoxide nanomaterial catalyst prepared in Comparative Example 2 are compared. 2 and 1A / cm 2 The overpotentials at the current density of 100 mA / cm 2 and 1A / cm 2 The overpotentials at current density of 100 mA / cm 2 and 1Acm 2 The overpotentials at 480 mV and 782 mV were shown, indicating that the material of the present invention has excellent OER catalytic activity.
[0069] Figure 4 Linear sweep voltammetric polarization curves of HER in potassium hydroxide (1M KOH) solution for the ruthenium cobalt solid solution oxide nanofiber material catalyst prepared in Example 2, the ruthenium dioxide nanofiber material catalyst prepared in Comparative Example 1, and the cobalt tetraoxide nanomaterial catalyst prepared in Comparative Example 2. 2 and 1A / cm 2 The overpotentials at the current density of 100 mA / cm 2 and 1A / cm 2 The overpotentials at the current density of 100 mA / cm 2 The overpotential is 574 mV); and the electrocatalytic hydrogen evolution performance of the cobalt tetroxide nanomaterial catalyst is significantly reduced, and it is difficult to achieve a higher current density; indicating that the material of the present invention has excellent HER catalytic activity.
[0070] Figure 5 The time-current curve of OER of the ruthenium cobalt solid solution oxide nanofiber material catalyst prepared in Example 1 in potassium hydroxide (1MKOH) solution. At a current density of 1A / cm 2 When the catalyst is used as a catalyst, it can be stable for 120 h with almost no significant decay in current density. This shows that the material of the present invention has excellent stability for the OER process at industrial-level high current density.
[0071] Figure 6This is the time-current curve of HER of the ruthenium cobalt solid solution oxide nanofiber material catalyst prepared in Example 2 in potassium hydroxide (1M KOH) solution. At a current density of 1A / cm 2 When the catalyst is heated to 100 ℃ and the current density is almost not significantly decreased, the catalyst can be stable for 120 hours, indicating that the material of the present invention has excellent stability for the HER process at industrial-level high current density.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a ruthenium-cobalt solid solution oxide nanofiber material, the steps of which are as follows: A. Preparation of nanofiber membrane by electrospinning: A1. Dissolve 0.2-0.4 g polyvinyl pyrrolidone, a certain mass of cobalt salt and ruthenium salt in 2-5 mL of a mixed solution of N,N-dimethylformamide and ethanol, wherein the amount of N,N-dimethylformamide or ethanol can be 0, and stir for 12 hours to obtain a uniform viscous spinning solution precursor; A2, injecting the viscous spinning solution precursor in step A1 into the syringe of the electrospinning device, performing electrospinning at a spinning distance of 15 to 30 cm and a spinning voltage of 12 to 25 kV, and obtaining a nanofiber membrane on an aluminum foil receiving plate; B. Calcine the nanofiber membrane obtained in step A2 in air at 200-500° C. for 2-4 hours to obtain a ruthenium-cobalt solid solution oxide nanofiber material.
2. The method for preparing a ruthenium-cobalt solid solution oxide nanofiber material according to claim 1, characterized in that: The mass ratio of the total mass of the cobalt salt and the ruthenium salt to the polyvinyl pyrrolidone in step A1 is 1:
1.
3. The method for preparing a ruthenium-cobalt solid solution oxide nanofiber material according to claim 1, characterized in that: The molar ratio of the cobalt salt to the ruthenium salt in step A1 is 1:(1-3).
4. The method for preparing a ruthenium-cobalt solid solution oxide nanofiber material according to claim 1, characterized in that: In step A1, the cobalt salt is one of cobalt acetate, cobalt nitrate or cobalt chloride; the ruthenium salt is one of potassium chlororuthenate, ruthenium chloride or ammonium chlororuthenate.
5. The method for preparing a ruthenium-cobalt solid solution oxide nanofiber material according to claim 1, characterized in that: The molecular weight of polyvinyl pyrrolidone in step A1 is 1000-1500 kDa.
6. A ruthenium-cobalt solid solution oxide nanofiber material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 5.
7. The ruthenium-cobalt solid solution oxide nanofiber material according to claim 6, characterized in that: The ruthenium-cobalt solid solution oxide nanofiber is a one-dimensional material with a diameter of 100-400nm and a length greater than 5μm.
8. Use of the ruthenium cobalt solid solution oxide nanofiber material according to claim 6 in alkaline electrocatalytic hydrogen and oxygen evolution at industrial-grade current density.
Citation Information
Patent Citations
Bimetal-doped metal phosphide nanofiber and preparation method thereof
CN112877812A
FeCoNi-MnRu high-entropy alloy / carbon nanofiber electro-catalytic material for full-pH hydrogen evolution reaction
CN113549946A
Metal oxide water oxidation catalyst with nanofiber structure of core-shell shape containing ruthenium oxide and cobalt oxide particles and manufacturing method thereof
KR101484733B1
Cited By
Cobaltosic oxide loaded ruthenium dioxide fiber as well as preparation method and application thereof
CN120119281A